Development of a Structural Model for Drug Use Tendency Based on Perceived Social Support and Behavioral Inhibition/Activation Systems (BAS/BIS) with the Mediation of Perceived Stress - Rostami, Morad; Kadivar, Parvin; Sharifirad, Gholamreza (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to develop a structural model of drug use tendency based on perceived social support and behavioral inhibition/activation systems (BAS/BIS), mediated by perceived stress in adolescent girls in Tehran. Methodology: In the current correlational-descriptive study, the statistical population of the study consisted of female adolescent students aged 14 to 18 from districts 5, 7, and 15 of Tehran, with an approximate number of 35,000 individuals selected during the second half of 2023. A multistage random sampling method was employed in this research. First, districts 5, 7, and 15 of Tehran were randomly selected, followed by the random selection of two high schools for girls from each district. Finally, based on the Krejcie and Morgan table and considering the population size, three classes were randomly selected from each high school, and 20 students were randomly chosen from each class, resulting in a total sample of 360 participants. Correlation tests, regression, and structural equation modeling were used for data analysis. Findings: The results showed that perceived stress plays an indirect mediating role in the relationship between perceived social support and drug use tendency in adolescent girls in Tehran. Additionally, it was found that perceived stress indirectly mediates the relationship between behavioral inhibition/activation systems and drug use tendency in adolescent girls in Tehran. The goodness-of-fit test for the structural equation model indicated that the Gof value was 0.69, reflecting a strong overall fit for the model. Conclusion: The findings of this study demonstrate that perceived stress significantly mediates the relationship between both perceived social support and Behavioral Inhibition/Activation Systems (BIS/BAS) and drug use tendency in adolescent girls.